Avaliação do pH, liberação de íons cálcio e atividade antibacteriana de um material retrobturador de polimerização dual à base de Bis-EMA/MTA - Linhares, Giane da Silva (2012)
The incorporation of light-curable resins has been proposed for Mineral Trioxide Aggregate (MTA) to improve its properties and reduce its setting time. The aim of the present study was to assess the pH, calcium-ion release and antibacterial activity of an experimental dual-cure Bis-EMA/MTA-based root-end filling material (E-MTA) in comparison with white-MTA (W-MTA); and to evaluate the influence of the addition of CaCl2 on these properties. Polyethylene tubes filled with the materials were immersed in deionized water for the measurement of pH (digital pH meter) and calcium release (atomic absorption spectrophotometry). The evaluations were performed at 3 and 24 hours and 7, 15 and 30 days. The direct contact test was used for evaluation of antibacterial activity of the materials against E. faecalis 30 min and 24 h after manipulation. All materials presented a variation from an alkaline to nearly neutral pH, and were capable of releasing calcium ions along the 30 days of the study. E-MTA showed a significant lower calcium ion release capacity when compared to W-MTA (P<0.05). The calcium release of E-MTA + 5% CaCl2 was similar to W-MTA (P> 0.05). All materials were 100% effective against E. faecalis at 30 min after manipulation. Reduction in the antibacterial activity was observed for E-MTA with or without the addition of CaCl2 after 24h. The monomer Bis-EMA added to MTA formed a material with lower capacity of calcium release and lower antibacterial activity than W-MTA, in spite of maintaining a similar pH. However, the addition of CaCl2 improved the calcium release of this material